أهمية مادة فقه اللغة العربية في تعليم اللغة العربية - Rodhy Harisca (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
The objectives of this article is to classify the importance of Arabic philology subject in teaching Arabic language and to explain the basic theory of Arabic philology (its concept, topics, and issues). The article adopted the descriptive method as the researcher analyzed the importance of Arabic philology in teaching Arabic language. The article findings indicated that Arabic philology subject has an important value and useful in the field of teaching Arabic language, as discussing about Arabic language matters. Based on the research findings, the researcher recommended conducting a research study about the rest contents of this subject for achieving the educational goals. In order to face global interaction using Arabic language which known as one of the international languages and then later to understand the message of Islam which originated in Arabic.